Improving the management and referral of patients with transient ischaemic attacks: a change strategy for a health community. Issue 1 (2nd February 2006) - Wright, J; Harrison, S; McGeorge, M; Patterson, C; Russell, I; Russell, D; Small, N; Taylor, M; Walsh, M; Warren, E; Young, J
Abstract : Problem: Rapid referral and management of patients with transient ischaemic attacks is a key component in the national strategy for stroke prevention. However, patients with transient ischaemic attacks are poorly identified and undertreated. Design and setting: Before and after evaluation of quality improvement programme with controlled comparison in three primary care trusts reflecting diverse populations and organisational structures in an urban district in the North of England. Key measures for improvement: The proportion of patients receiving antiplatelet drugs and safe driving advice on referral to a speciality clinic, and the numbers of referrals, adjusted for age, to the specialist clinic before and after the improvement programme. Strategies for change: Interviews with patient and professionals to identify gaps and barriers to good practice; development of evidence based guidelines for the management of patients with transient ischaemic attacks; interactive multidisciplinary workshops for each primary care trust with feedback of individual audit results of referral practice; outreach visits to teams who were unable to attend the workshops; referral templates and desktop summaries to provide reminders of the guidelines to clinicians; incorporation of standards into professional contracts. Effects of change: A significant improvement occurred in identification and referral of patients with transient ischaemic attacks to specialist clinics, with a 41% increase in referrals from trained practices compared with control practices. There were also significant improvements in the early treatment and safety advice provided to patients before referral. Lessons learnt: A strategic approach to effective quality improvement across a diverse health community is feasible and achievable. Careful planning with patient and professional involvement to develop a tailored and multifaceted quality improvement programme to implement evidence based practice can work in very different primary care settings. Key components of the effectiveness of the model include contextual analysis, strong professional support, clear recommendations based on robust evidence, simplicity of adoption, good communication, and use of established networks and opinion leaders.